Women Empowerment: The Backbone of Economic and Social Progress - D. S. Nittur, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Women empowerment is not just a matter of social justice; it is an essential pillar of sus-tainable economic development. Despite contributing significantly to society and the economy both visibly and invisibly women in many parts of India still face systemic challenges such as illiteracy, low wages, and social discrimination. This paper discusses the multifaceted roles women play in the economic, cultural, and political development of a nation. It also sheds light on their current socio-economic conditions and the various government schemes aimed at empowering them. Through education, policy support, and grassroots programs, India can harness the untapped po-tential of women and drive forward toward inclusive and equitable growth.
Keywords: IFAD; SHGs; STEP; FLFPR; PMKVY; RMK